Sources of Information for Social Studies Teachers and Their Level of Usage in Abeokuta, Ogun State Nigeria - Amos, Adediran Adekunle; Abdukareem, Y. (Richtmann Publishing, 2012)
The study examined sources of information for teachers in social studies and their level of usage insecondary schools. The design of this study was descriptive of survey type. Data was collected from twentyfour(24) secondary schools and was randomly selected from Abeokuta north local government andAbeokuta south local government area of Ogun state, Nigeria. A total of ninety-seven (97) secondaryschools female and male teachers of different age- grades, qualifications and experience were used assample. Questionnaire was made use of for data collection. The questionnaire was the close ended likerttypetechnique that expresses degree of agreement or disagreement with he supplied statement. Data wasanalyzed using standard deviation, students- t-test statistics, mean and rank order. The findings of thestudy revealed that, teachers’ sources of information for social studies include reference materials, newspapers, journals, literary materials, historical monuments and artifacts, television, textbooks, resourceperson, magazines, pamphlet, bulletins and radio. Computer component, such as e-mail, file transferprotocol, World Wide Web (www) rarely used by social studies teachers. Recommendations were madewhich includes computer training be provided for social studies teachers at all level of education in Nigeriaand modern information centers with integrated circuits and digital communication to link schools shouldbe provided at local levels for the use of teachers, particularly for social studies teachers.